Retrospective Study of Traumatic Intra-Interspecific Interactions in Stranded Cetaceans, Canary Islands - Puig-Lozano, Raquel; Fernández, Antonio; Saavedra, Pedro; Tejedor, Marisa; Sierra, Eva; De la Fuente, Jesús; Xuriach, Aina; Díaz-Delgado, Josué; Rivero, Miguel Antonio; Andrada, Marisa; Bernaldo de Quirós, Yara; Arbelo, Manuel (Frontiers in Veterinary Science, 2020)
Aggressive encounters involving cetacean species are widely described in the literature. However, detailed pathological studies regarding lesions produced by these encounters are scarce. From January 2000 to December 2017, 540 cetaceans stranded and were necropsied in the Canary Islands, Spain. Of them, 24 cases of eight species presented social traumatic lesions produced by cetaceans of the same or different species. All the cases presented severe multifocal vascular changes, 50% (12/24) presented fractures affecting mainly the thoracic region, 41.7% (10/24) acute rake marks, 37.5% (9/24) non-digested food in the stomach, 33.3% (8/24) tracheal edema, and 12.5% (3/24) pulmonary perforation. In ten cases with rake marks, the distance between the teeth, allowed us to further identified the aggressor species: four cases were compatible with killer whales (Orcinus orca) affecting three species [pigmy sperm whale (Kogia breviceps), Cuvier’s beaked whale (Ziphius cavirostris) and short-finned pilot whale (Globicephala macrorhynchus)] and four cases compatible with common bottlenose dolphins (Tursiops truncatus) affecting two species [short-beaked common dolphin (Delphinus delphis) and Atlantic spotted dolphin (Stenella frontalis)]. We also described two cases of intraspecific interaction in stripped dolphin (Stenella coeruleoalba). Microscopically, 70.8% (17/24) of the cases presented acute degenerative myonecrosis, 66.7% (14/21) presented vacuoles in the myocardiocytes, 36.8% (7/19) pigmentary tubulonephrosis, 31.6% (6/19) cytoplasmic eosinophilic globules within hepatocytes, 21.4% (3/14) hemorrhages in the adrenal gland, and 17.3% (4/23) bronchiolar sphincter contraction. The statistical analysis revealed that deep divers, in good body condition and nearby La Gomera and Tenerife were more prone to these fatal interactions. Additionally, in this period, three animals died due to an accident during predation: a false killer whale (Pseudorca crassidens) died because of a fatal attempt of predation on a stingray, and two Risso’s dolphins (Grampus griseus) died as a consequence of struggling while predating on large squids.